Flux simulation on 100kVA three-phase transformer core - Dina Maizana, Maiz Ahmad, Ir.; Ismail, Daut, Prof. Dr.; Soib, Taib (Praise Worthy Prize S.r.l., 2011)
Link to publisher's homepage at http://www.praiseworthyprize.com/